METHODOLOGICAL SIGNIFICANCE OF THE SYSTEMIC-SYNERGETIC APPROACH TO DETERMINING THE INTEGRATION OF SMALL AND LARGE ENTERPRISES - Akhmedova Nilufar Shukhratovna (Modern American Journals, 2025)
This article is devoted to analyzing the methodological foundations for studying the integration of small and large enterprises in the context of socio-economic development. The study examines the system of cooperative relations between enterprises through the lens of a systemic-synergetic approach. While the systemic approach determines the static and hierarchical structure of the system, synergetics substantiates its nonlinear development dynamics, self-organization mechanisms, and development in a non-equilibrium state. The article highlights the differences between cybernetic and synergetic approaches and emphasizes the role of positive feedback in the integration process. The analysis concludes by proposing a conceptual research plan based on a systemic-synergetic approach for studying the union of small and large enterprises.
Keywords: Small business, large enterprises, integration, systemic approach, synergetics, systemic-synergetic approach, cybernetics, self-organization, nonlinearity.